Switching Models with Self-Selection: Self-Employment in Hungary - Ira N. Gang; Catherine Y. Co; Myeong-Su Yun (Rutgers University, Department of Economics, 1999)
We estimate the determinants of earnings for both the self-employed and wage/salary sectors in an economy undergoing transition from socialism to greater market orientation. We adopt a (full information) MLE methodology in addition to Heckman's two-step method, while taking both participation and self-employment decisions into account. We use the Hungarian Household Panel Survey for 1994. We find that the return to characteristics are not significantly different between self-employed and wage/salary sectors. However, when we also account for the dispersion of earnings, the structure of the earnings between the self- and wage/salary employed are different
Keywords: C34; J31; P23; 330; decomposition; self-employment; self-selection; switching; transition